The Effectiveness of Progressive Muscle Relaxation Technique in Reducing Labor Pain During the First Stage of Active Phase - Neneng Siti Lathifah; Grestina Yuni Farida Simamora; Anggraini Anggraini (Jurnal Bidan Cerdas, 2026)
Background: In Indonesia, there are over 4 million births annually, with 7,503 occurring in Pesawaran District and 720 in Kedondong Public Health Center.  A preliminary survey at Kedondong Public Health Center revealed that most women experienced moderate to severe pain (pain scale 5–8). Existing interventions such as breathing techniques, spousal support, and positive suggestions have not been optimally effective in reducing pain. Progressive muscle relaxation (PMR), a non-pharmacological technique combining deep breathing with alternating muscle contraction and relaxation, is believed to reduce pain transmission and improve oxygen flow. Methods: This quantitative study used a quasi-experimental two-group pretest-posttest design. The population consisted of 51 laboring mothers at independent midwifery practices (PMB) in the Kedondong Health Center working area. A total of 32 participants were selected using accidental sampling and divided equally into intervention and control groups (16 each). Data were collected using observation sheets and analyzed using univariate and bivariate methods (Mann-Whitney test). Results: The univariate analysis showed that the average pain score in the intervention group before the relaxation technique was 7.06 and decreased to 5.44 after the intervention. In the control group, the average pain score before was 6.63 and slightly decreased to 6.00. The results indicated that progressive muscle relaxation was effective in reducing labor pain (p-value = 0.000). Conclusion: Progressive muscle relaxation is effective in reducing labor pain during the active phase of the first stage. Progressive muscle relaxation is applied as a non-pharmacological method to manage labor pain and increase maternal comfort and safety.